Peningkatan Minat Baca Peserta Didik Melalui Program Literasi di SDN Sidokare 1 Sidoarjo - Firmansyah, Alfian; El-Yunusi, Muhammad Yusron (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Reading interest is one of the key factors in developing learners' literacy skills. A literacy program can be one solution to this problem that not only focuses on teaching reading but also creates an atmosphere that supports reading interest. The purpose of the study was to find out how much impact the school literacy program has on students' interest in reading at SDN Sidokare 1 Sidoarjo. This research uses qualitative research methods with the target of Principals, Teachers and students in the environment of SDN Sidokare 1 Sidoarjo with data collection techniques through interviews, observation and documentation through recording and collecting data from the subject of observation. Based on the results of the research, the school library program has a positive impact on students' interest in reading. There are obstacles faced by limited resources, both in the form of books, facilities and infrastructure, technology and qualified educators. School efforts in dealing with these obstacles by providing socialization, adding facilities and infrastructure and collaborating with related agencies (regional library office) to support the activeness of students' interest in reading at SDN SIdokare 1.